Activation of NOD1 and NOD2 in the development of liver injury and cancer - Omaru, Naoya; Watanabe, Tomohiro; Kamata, Ken; Minaga, Kosuke; Kudo, Masatoshi (Frontiers in Immunology, 2022)
Hepatocytes and liver-resident antigen-presenting cells are exposed to microbe-associated molecular patterns (MAMPs) and microbial metabolites, which reach the liver from the gut via the portal vein. MAMPs induce innate immune responses via the activation of pattern recognition receptors (PRRs), such as toll-like receptors (TLRs), nucleotide-binding oligomerization domain 1 (NOD1), and NOD2. Such proinflammatory cytokine responses mediated by PRRs likely contribute to the development of chronic liver diseases and hepatocellular carcinoma (HCC), as shown by the fact that activation of TLRs and subsequent production of IL-6 and TNF-α is required for the generation of chronic fibroinflammatory responses and hepatocarcinogenesis. Similar to TLRs, NOD1 and NOD2 recognize MAMPs derived from the intestinal bacteria. The association between the activation of NOD1/NOD2 and chronic liver diseases is poorly understood. Given that NOD1 and NOD2 can regulate proinflammatory cytokine responses mediated by TLRs both positively and negatively, it is likely that sensing of MAMPs by NOD1 and NOD2 affects the development of chronic liver diseases, including HCC. Indeed, recent studies have highlighted the importance of NOD1 and NOD2 activation in chronic liver disorders. Here, we summarize the roles of NOD1 and NOD2 in hepatocarcinogenesis and liver injury.